Corporate Governance Mechanisms in Commercial Banks of Nepal - Baral, Ravindra Prasad (Janapriya Journal of Interdisciplinary Studies, 2020)
Corporate governance in banking sector has received great attention among policymakers, practitioners and academicians in Nepal due to governance failures in some financial institutions in recent period. This study attempts to examine the corporate governance mechanisms adopted by Nepalese commercial banks by using a panel data of 30 commercial banks from 2012 to 2016. The internal corporate governance mechanisms are board structure and composition, board committees, director independence, transparency and disclosure, director remuneration, and shareholders rights. The study employs ANOVA test to examine differences in corporate governance mechanisms among state-owned, joint venture, and domestic banks. The study findings reveal that the corporate governance practices in financial institutions of Nepal is somewhat satisfactory; however, significant improvements are required especially in case of state-owned banks and local private banks. In order to achieve the policy of government of Nepal to enhance financial system stability, one of the major areas for policy focus should be to promote enhancement of corporate governance standards in the financial institutions as the stability of the banking sector depends largely on corporate governance practices they adopt. Promoting director independence, improving transparency and disclosure, and enhancing shareholders’ right are found to be important for improving standard of corporate governance in Nepal.